Defects in High Pressure Die Casting Process - Podprocká, Radka; Malik, Jozef; Bolibruchová, Dana (Manufacturing Technology Journal, 2015)
Pressure die casting of metals is a method of precise metal casting, where molten liquid metal is forced under high pressure into a mould cavity. Requirements of engineering and automotive industries for perfect castings with smooth surfaces, exact dimensions and thin walls determine the nature and direction of development of pressure die casting of metal. This article analyses the possible causes of a foundry defect - short run - generated during casting based on varying technological parameters.
Keywords: cast; short run; mold; temperature